Descriptions of larvae of Caliphaea angka Hämäläinen, 2003 and Mnais gregoryi Fraser, 1924 (Odonata: Calopterygidae) - Yang, Guo-Hui; Zhang, Hao-Miao; Orr, Albert G. (Zootaxa, 2021)
The larvae of Caliphaea angka Hämäläinen, 2003 and Mnais gregoryi Fraser, 1924 are described and illustrated for the first time from Erhai lake Basin, Yunnan Province, China. Notes on their habitat are provided. This paper represents the first verified description of the larva of Caliphaea Hagen in Selys, 1859.